2021
DOI: 10.1002/col.22705
|View full text |Cite
|
Sign up to set email alerts
|

Exploring color attractiveness and its relevance to fashion

Abstract: Many studies have been conducted on the phenomenon of color preference,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
(54 reference statements)
0
9
1
1
Order By: Relevance
“…According to Fulcher and Hayes ( 2018 ), Yeung and Wong ( 2018 ), the color range of pink and purple was a preference for females, while blue and green for males. Kodžoman et al ( 2022 ), Kuo et al ( 2022 ) also presented color ranges of pink and blue as colors with preference highest levels among women and men, respectively. Based on these classic scales and color ranges, the male scale taken as a basis was proposed by Silver and Ferrante ( 1995 ), presenting color preferences for masculine colors in shades of green and blue.…”
Section: Methodsmentioning
confidence: 98%
“…According to Fulcher and Hayes ( 2018 ), Yeung and Wong ( 2018 ), the color range of pink and purple was a preference for females, while blue and green for males. Kodžoman et al ( 2022 ), Kuo et al ( 2022 ) also presented color ranges of pink and blue as colors with preference highest levels among women and men, respectively. Based on these classic scales and color ranges, the male scale taken as a basis was proposed by Silver and Ferrante ( 1995 ), presenting color preferences for masculine colors in shades of green and blue.…”
Section: Methodsmentioning
confidence: 98%
“…Other research on color concerns perceivers' color preferences across time and place. A recent review of color preferences over time (Kodžoman et al, 2021) suggests that Western color preferences for dress have shown some stability over the past 100 years, with blue and red DRESS IN PERSON PERCEPTION 35 ranking higher in preference. However, the review points out some methodological limitations and finds that current color preferences for dress include yellow, pink, and black.…”
Section: Integration Of Existing Dress Researchmentioning
confidence: 99%
“…However, the review points out some methodological limitations and finds that current color preferences for dress include yellow, pink, and black. Gender differences also emerge, with women rating yellow and white more highly than men ( Kodžoman et al, 2022 ). Outside of scientific dress research, it is worth noting that preferences for dress clearly vary across time and place.…”
Section: Factors Of Dress In Person Perceptionmentioning
confidence: 99%
“…Very Peri demonstrates the confidence and daring curiosity of being at ease, symbolising people embracing a future full of possibilities. It expresses the determination to live with the novel coronavirus epidemic and the hope for the future in the post-epidemic era (Kodžoman et al 2022). This popular colour is reflected in the home furnishing sector, with a number of leading international furniture companies bringing beautiful new colour ranges to the 2022 Milan Furniture Fair.…”
Section: Trends In the Visual Art Of Wooden Doorsmentioning
confidence: 99%